Studies On Early Compressive Strength Of ECC Mortar Composed By Rice Husk Ash And Silica Fume - Muhammad Rizki Harahap; Muhammad Aswin (Syntax Corporation, 2022)
In general, mortars have low characteristics and performance. Mortar technology is constantly evolving for better achievements. Meanwhile, there is a lot of waste or residual production materials that has not been used optimally. Related to that, in this research, the utilization of these waste materials, including silica fume and rice husk ash has been carried out. Cylindrical specimens with a diameter of 100 mm and a height of 200 mm were prepared in 16 variations of mixes proportion, where the addition percentage of silica fume (SF) and rice husk ash (RHA) were 0%, 5%, 10% and 15% respectively by weight of cement. In this study, mechanical properties only considered the early compressive strength at the age of 1 day, while flowability was conducted to check the consistency of the fresh mixes of engineered cementitious composites (ECC) mortar. The test results show that the workability of the ECC mortar is in accordance with the European Federation of National Associations Representing for Concrete (EFNARC) standard. Meanwhile, the optimum compressive strength of ECC mortar at the age of 1 day was achieved in ECC mortar with RHA proportion of 0% and 5% combined by SF of 15%. Higher percentage of RHA or SF, can lead to decrement the early compressive strength of ECC mortar.